2011
DOI: 10.1186/1471-244x-11-12
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the rhythm of depression using Mobile Cognitive Therapy for recurrent depression: randomized controlled trial design and protocol

Abstract: BackgroundMajor depressive disorder (MDD) is projected to rank second on a list of 15 major diseases in terms of burden in 2030. The major contribution of MDD to disability and health care costs is largely due to its highly recurrent nature. Accordingly, efforts to reduce the disabling effects of this chronic condition should shift to preventing recurrence, especially in patients at high risk of recurrence. Given its high prevalence and the fact that interventions are necessary during the remitted phase, new a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…medication, behavioral therapy, exercise) on several outcomes, including positive mood (Goyal et al, 2014). Currently, larger scale trials are in progress to address the question whether a psychological intervention can be an alternative for continuation/maintenance ADMs (MOMENT study, Huijbers et al, 2012;PREVENT study, Kuyken et al, 2010; Break the rhythm of depression study, Bockting, Elgersma, et al, 2011;Bockting, Kok, et al, 2011).…”
Section: Indicated Psychological Relapse Prevention Strategies After mentioning
confidence: 97%
See 1 more Smart Citation
“…medication, behavioral therapy, exercise) on several outcomes, including positive mood (Goyal et al, 2014). Currently, larger scale trials are in progress to address the question whether a psychological intervention can be an alternative for continuation/maintenance ADMs (MOMENT study, Huijbers et al, 2012;PREVENT study, Kuyken et al, 2010; Break the rhythm of depression study, Bockting, Elgersma, et al, 2011;Bockting, Kok, et al, 2011).…”
Section: Indicated Psychological Relapse Prevention Strategies After mentioning
confidence: 97%
“…Secondary prevention studies within randomized controlled trials, including tests of mediation, continue to be needed to establish if such treatments work through their hypothesized mechanism (e.g. Batink, Peeters, Geschwind, van Os, & Wichers, 2013;Bockting, Elgersma, et al, 2011;Bockting, Kok, et al, 2011;Kuyken et al, 2010;Williams et al, 2014).…”
Section: Recurrencementioning
confidence: 99%
“…In order to be included in the randomized controlled trial [33], participants had to: (1) be between 18 and 65 years old and (2) be in remission/recovery from recurrent MDD for at least 2 months but not longer than 2 years according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR) as assessed using the Structured Clinical Interview (SCID-I) based on the DSM-IV-TR [34] and a maximum score of 10 on the 17-item Hamilton Rating Scale for Depression (HRSD 17 ) [35]. Further, participants had to have Internet access.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this single-blind 2-arm parallel randomized controlled trial (trial registration NTR2503; approved by METIGG, an independent medical ethics committee) was to examine whether adding M-CT to TAU is clinically superior to TAU alone over 24 months (primary outcome) in remitted recurrently depressed individuals. Details about the study design can be found elsewhere [7]. …”
Section: Figmentioning
confidence: 99%